Two-step protein labeling by using lipoic acid ligase with norbornene substrates and subsequent inverse-electron demand Diels-Alder reaction - Best, Marcel; Degen, Anna; Baalmann, Mathis; Schmidt, Tobias Thomas; Wombacher, Richard (ChemBioChem, 2015)
Abstract Inverse-electron-demand Diels?Alder cycloaddition (DAinv) between strained alkenes and tetrazines is a highly bio-orthogonal reaction that has been applied in the specific labeling of biomolecules. In this work we present a two-step labeling protocol for the site-specific labeling of proteins based on attachment of a highly stable norbornene derivative to a specific peptide sequence by using a mutant of the enzyme lipoic acid ligase A (LplAW37V), followed by the covalent attachment of tetrazine-modified fluorophores to the norbornene moiety through the bio-orthogonal DAinv?. We investigated 15 different norbornene derivatives for their selective enzymatic attachment to a 13-residue lipoic acid acceptor peptide (LAP) by using a standardized HPLC protocol. Finally, we used this two-step labeling strategy to label proteins in cell lysates in a site-specific manner and performed cell-surface labeling on living cells.
Gesehen am 22.05.2020